Digital Era Education System at the West Bandung Regency Education Office (Dynamic Governance Study) - Indriasari, Santy Kusumawati; Rohayati, Yeti; Setiawan, Awan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to determine how the digital era education system in the West Bandung district education office through dynamic governance study through aspects of the study of responsiveness, adaptivity, increasing capacities, multisectoral collaboration, policy evaluation, reflection and recommendations, This research uses research design descriptive qualitative with methods interviews, observation, and documentation studies where the results of the research will be processed until saturated and find the results of the research. The results show that the digital divide and limited access in remote areas are still obstacles that need to be overcome. Co-operation between the government, private sector and communities is essential to create an inclusive and adaptive education ecosystem. Thus this research is expected to help in providing an understanding of the education system in the digital era at the Education Office in West Bandung Regency.